Influence of minerals on lead-induced alterations in liver function in rats exposed to long-term lead exposure - Herman, D'souza Sunil; Geraldine, Menezes; T, Venkatesh (Journal of hazardous materials, 2009)
The objective of this study was to evaluate the role of minerals on lead-induced effect on the liver. Differentiation of minerals and heavy metals pose an inherent problem due to certain common properties shared by them. With this approach to the problem of heavy metal toxicity, in the present study two groups of male Wistar albino rats, one group (well-nourished) fed on mineral rich diet and other group (undernourished) fed on diet without mineral supplements were used. Both the groups of rats were subjected to long-term lead exposure. The diet of well-nourished group was supplemented with calcium (Ca); 1.2%, phosphorous (P); 0.6%, iron (Fe); 90 mg/kg, zinc (Zn); 50 mg/kg, magnesium (Mg); 0.08%, manganese (Mn); 70 mg/kg, selenium (Se); 0.2 mg/kg, copper (Cu); 5 mg/kg, molybdenum (Mo); 0.8 mg/kg, iodine (I); 0.6 mg/kg, cobalt (Co); 3.0 mg/kg. Their blood lead and parameters of liver function were monitored periodically. Results of the study showed a very high statistically significant increase ( p < 0.001) in the blood lead (PbB) levels and liver function test parameters in the undernourished subjects compared to the well-nourished subjects. Nutritional management of lead poisoning is of importance since essential elements and toxic heavy metals may interact to minimize the absorption of lead.